2000
DOI: 10.1161/01.cir.102.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Efficacy of Dofetilide in Differing Experimental Models of Atrial Fibrillation

Abstract: The mechanism underlying AF importantly influences dofetilide efficacy. The dependence of drug efficacy in AF on the underlying mechanism has potentially significant implications for antiarrhythmic drug use and development and may explain the well-known therapeutic resistance of longer-duration AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 98 publications
(90 citation statements)
references
References 35 publications
(35 reference statements)
7
81
0
2
Order By: Relevance
“…20,57 CHF-related AF appears to arise, at least in some instances, from a single macroreentrant source. 58 Further work is needed to evaluate quantitatively the potential mechanisms of AF based on substrates other than increased cholinergic tone.…”
Section: Comparison With Experimental Studies Of Vagal Afmentioning
confidence: 99%
“…20,57 CHF-related AF appears to arise, at least in some instances, from a single macroreentrant source. 58 Further work is needed to evaluate quantitatively the potential mechanisms of AF based on substrates other than increased cholinergic tone.…”
Section: Comparison With Experimental Studies Of Vagal Afmentioning
confidence: 99%
“…We have recently shown that intravenous dofetilide increases ERP to a greater extent in the LA than in the RA in dogs with a substrate for AF caused by either congestive heart failure or sustained atrial tachycardia. 21 Dofetilide was highly effective in terminating heart failure-related AF but was relatively ineffective in AF associated with atrial tachycardia-induced remodeling. In the latter group, dofetilide largely eliminated reentrant activity in the LA, but persistent reentry in the RA maintained AF.…”
Section: Potential Significancementioning
confidence: 99%
“…[1][2][3][4][5][6][17][18][19][20] All studies showed strong ERP reduction and loss of rate adaptation. Changes in CV with long-term (several-week) atrial pacing have been variable, with some studies suggesting a decrease in CV 2,4,5 and others no change 1 ; however, no studies have shown that AT slows conduction significantly in normal hearts over a 1-week period.…”
Section: Relationship To Previous Observations Regarding Atrial Tachymentioning
confidence: 96%